Development and Characterization of Eclipta alba Infused Polyherbal Balm for Dermatological Inflammation and Hypersensitivity: Research Article (Journal of Pharma Insights and Research, 2026)
Eclipta alba, commonly known as Bhringraj, is a valuable traditional Ayurvedic medicine due to its high concentration of bioactive coumestans and alkaloids. The formulation of a topical balm incorporating ethanolic extracts of E. alba combined with adjuvant herbal agents like Curcuma longa offers a synergistic approach to managing dermal inflammation and allergic responses. Phytochemical screening of the prepared semi-solid matrix confirms the presence of alkaloids and flavonoids, which are instrumental in modulating pro-inflammatory mediators. Physicochemical evaluation shows a stable preparation with a pH of 6.5, coiniciding with the physiological range of human skin. Spreadability and homogeneity indices suggest an optimal consistency for topical application, ensuring effective dermal penetration of active phytoconstituents. The high total fatty matter content establishes the occlusive and emollient properties of the beeswax-coconut oil base, which serves to enhance skin barrier function. Standardized primary skin irritation assessments indicate a favorable safety profile, showing no signs of erythema or edema. Consistent stability under varied thermal conditions signifies the robust nature of the herbal formulation. The combination of traditional botanical knowledge with contemporary pharmaceutical technology yields a viable and safe alternative to synthetic topical anti-inflammatory agents